INFLUENCE OF JIGSAW MODEL WHICH COMBINED WITH PAPER OPERAND IDEA TECHNIQUE FOR SENIOR HIGH SCHOOL STUDENTS - Wanda Apri Yeni; Relsas Yogica (Universitas Negeri Padang, 2021)
The research is based on the problems in SMAN 4 Padang, the low learning competency of students. Learning competency is an ability that must be possessed by students to know what they have mastered during learning. In this study aims to observe the influence of the aplication of the jigsaw cooperative learning model combined with the paper operand technique of ideas on the learning competencies of students in class X MIA SMAN 4 Padang in the acedemic year 2019/2020. Forms of this study was Quasi Experimental Design with design Randomized Control Group Posttest Only Design. The population in this study were all students in grade X MIA SMAN 4 Padang. Sampling using purposive sampling. The data collection technique of learning outcomes using posttest and documentation. Learning outcomes data were analyzed by normality-test, f-test and t-test. The results showed that the average value learning competency experimental class is greater than the control class.